2019
DOI: 10.3389/fphar.2019.00244
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory T Cell Receptors PD1 and 2B4 Are Differentially Regulated on CD4 and CD8 T Cells in a Mouse Model of Non-alcoholic Steatohepatitis

Abstract: Infiltrating CD4 and CD8 T cells have been shown to worsen inflammatory liver damage in non-alcoholic steatohepatitis (NASH). Inhibitory T cell receptors such as the programmed cell death protein 1 (PD1) and the natural killer cell receptor 2B4 regulate the activity of CD4 and CD8 T cells and therefore play an important role in immune tolerance required in the liver. In this study, we investigated the expression profile of inhibitory T cell receptors on CD4 and CD8 T cells in a mouse model of NASH. Male B57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…It was recently shown that IL-13 producing cells, type 2 innate lymphoid cells (ILC2s), are destabilized in response to PD-1/PD-L1 pathway upon high-fat feeding resulting in impaired tissue metabolism [20]. Furthermore, PD-1 blockade showed a partial restore in type 2 innate axis and could serve as promising targets of immune-modulatory NASH therapy [21][22][23][24][25]. Importantly, PD-L1 was found to be responsible for HCC development in NASH via inducing the exhaustion of HCC-directed CD8 + T cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that IL-13 producing cells, type 2 innate lymphoid cells (ILC2s), are destabilized in response to PD-1/PD-L1 pathway upon high-fat feeding resulting in impaired tissue metabolism [20]. Furthermore, PD-1 blockade showed a partial restore in type 2 innate axis and could serve as promising targets of immune-modulatory NASH therapy [21][22][23][24][25]. Importantly, PD-L1 was found to be responsible for HCC development in NASH via inducing the exhaustion of HCC-directed CD8 + T cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…In mice fed an MCD, there was an increased frequency of Th17 cells in CD4 + T-cells in the liver tissue compared to that in the controls [279] . In this mouse model, the infiltration of Th17 cells in the liver triggered NASH pathogenesis and was important for the progression of liver fibrosis [119] . In MYC-ON mice fed with an MCD, the frequency of Th17 in liver tissue had increased compared to that in the controls [121] .…”
Section: Th17 Cells Increase In Liver Tissues In Various Nash Mouse Models and May Be Associated With Inflammation And Fibrosismentioning
confidence: 92%
“…In C57BL/6 mice that were fed a methionine-and choline-deficient (MCD) diet for 8 weeks, the frequency of CD4 + T-cells increased significantly over the 8 weeks in hepatic mononuclear cells of the liver tissue compared to that in the controls. From the second week onward, intrahepatic CD4 + T-cells were activated (evaluated by CD25) with the progression in the pathological conditions [119] . Furthermore, in C57BL/6 mice that were fed an MCD diet for 8 weeks, the frequencies of CD4 + T-cells and CD8 + T-cells in CD45 + cells that respond to oxidative stress-derived antigens increased in the liver tissue over time, and CD3 + T-cells were activated (evaluated by CD69).…”
Section: The Dynamics Of the Intrahepatic Cd4 + T-cell In The Nash Mouse Model Are Controversialmentioning
confidence: 99%
See 2 more Smart Citations